Improvement of Grid Independence Test for Computational Fluid Dynamics Model of Building Based on Grid Resolution - Minhyung Lee; Gwanyong Park; Changyoung Park; Changmin Kim (Advances in Civil Engineering)
Computational fluid dynamics (CFD) is being used in various research fields on the building environment. Target space of the CFD model is divided into a finite number of grids for numerical analysis. Therefore, an optimal grid design is required to obtain accurate results. The grid independence test is generally performed to design an optimal grid. However, given that there is no standardized procedure for gird independence test, most depend on the researcher’s experience and knowledge. In the conventional method, the subjective judgment of the researcher affected the selection of the grid conditions and the criteria for the optimal grid. It can lead to a decrease in the reliability of the simulation results by poor grid design. This study proposed a grid independence test method that applies the grid resolution to improve the conventional method. The grid resolution was calculated by applying the characteristic length. CV(RMSE) and R2 were applied as the criteria for optimal grid. A case study was conducted to evaluate the adequacy of the proposed method. As the characteristic length increased, the optimal grid resolution increased. In particular, for a characteristic length of 0.7 or more, the optimal grid resolution was evaluated as 24. The grid convergence index (GCI) was calculated to verify the suitability of the proposed method. As a result, all of the optimal grid resolution derived from the proposed method was evaluated as the optimal condition.